PROSEDUR PEMERIKSAAN RADIOGRAFI SHOULDER JOINT DENGAN KLINIS OSTEOARTHRITIS PROYEKSI AP METODE ROCKWOOD DI INSTALASI RADIOLOGI RS INDRIATI - Alifia Permata Sari,; Ike Ade Nur Liscyaningsih,; Taufiq Fachruddin Zen, (Journal of Innovation Research and Knowledge, 2025)
Radiography of the shoulder joint is a supportive examination to assess the condition of the shoulder joint structures, particularly in patients with osteoarthritis. Osteoarthritis is a degenerative joint disease characterized by pain, stiffness, and changes in joint shape, which can interfere with daily activities. This condition is one of the pathologies that can be detected through shoulder joint examination using the Rockwood method. This study aims to determine the procedure for shoulder joint examination using the Anteroposterior (AP) projection with the Rockwood method at Indriati Hospital of Solo Baru. The use of the AP projection with the Rockwood method is considered sufficient to assess the structure and stability of the acromioclavicular joint without the need for additional projections. This method is chosen because it avoids rotation that may cause pain, provides clear visualization, and is safer, more comfortable, and efficient for patients with pain or limited mobility. The research employed was qualitative, employing data collection techniques such as observation, documentation, and interviews with three radiographers and one radiologist. Data analysis was conducted using source triangulation and technique triangulation, then presented in narrative form and conclusions were drawn. The radiographic examination of the shoulder joint in osteoarthritis patients at Indriati Hospital of Solo Baru utilized the AP projection with the Rockwood method, positioning the patient standing and angling the beam 35° caudal. The examination was performed without special preparation, only requiring the removal of metallic objects. The resulting image showed a distance of 5.3 mm from the acromion to the humeral head, indicating joint space narrowing, consistent with the characteristics of osteoarthritis. This method was deemed effective as it provided clear visualization without extreme rotation and was sufficient for establishing a diagnosis